2014
DOI: 10.1177/1470320314545777
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curcumin on angiotensin-converting enzyme gene expression, oxidative stress and anti-oxidant status in thioacetamide-induced hepatotoxicity

Abstract: Curcumin treatment reduced oxidative stress in animals by scavenging reactive oxygen species, protecting the anti-oxidant enzymes from being denatured and reducing the oxidative stress marker lipid peroxidation. Curcumin treatment restores hepatocytes, damaged by TAA, and protects liver tissue approaching cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 25 publications
3
23
0
1
Order By: Relevance
“…These findings are in harmony with results of Ali et al, (2016) who indicated significant decreases in serum aminotransferases, and total and direct bilirubin levels in rats group given curcumin when compared to the untreated TAA intoxicated group. In another study , a significantly lower level was observed for the liver-specific enzymes(AST, ALT and ALP) in rats group treated with TAA and curcumin compared with the TAA-treated group (Fazal et al, 2014). Serum levels of transaminases return to normal may be a consequence of healing of hepatic parenchyma, stabilization of plasma membrane regeneration of hepatocytes, as well as repair of hepatic tissue damage caused by TAA (Palanivel, 2008, Vadivu et al, 2010, Moustafa et al, 2014.…”
Section: Discussionmentioning
confidence: 94%
“…These findings are in harmony with results of Ali et al, (2016) who indicated significant decreases in serum aminotransferases, and total and direct bilirubin levels in rats group given curcumin when compared to the untreated TAA intoxicated group. In another study , a significantly lower level was observed for the liver-specific enzymes(AST, ALT and ALP) in rats group treated with TAA and curcumin compared with the TAA-treated group (Fazal et al, 2014). Serum levels of transaminases return to normal may be a consequence of healing of hepatic parenchyma, stabilization of plasma membrane regeneration of hepatocytes, as well as repair of hepatic tissue damage caused by TAA (Palanivel, 2008, Vadivu et al, 2010, Moustafa et al, 2014.…”
Section: Discussionmentioning
confidence: 94%
“…CURa natural compoundhas attracted more and more attention for as an anti-oxidant. Results from Fazal et al 28 .…”
Section: Discussionmentioning
confidence: 95%
“…CUR – a natural compound – has attracted more and more attention for as an anti‐oxidant. Results from Fazal et al . showed that CUR could reduce oxidative stress in animals by scavenging ROS, protect the anti‐oxidant enzymes from being denatured and reduce the oxidative stress marker lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The TAA-induced hepatic injury and HE have been established in many studies biochemically and histologically with increased blood ammonia levels (Zimmermann et al 1989;Abdel-hameed et al 2014;Stefanello et al 2015 andLebda et al 2018). They reported oxidative damage in liver and brain tissues indicated by increased intracellular reactive oxygen species (ROS) production (Bruck et al 2004;Fazal et al 2015 andStefanello et al 2015). These "ROS" interfere with energy utilization by exerting toxic effects on the liver mitochondria (Chu et al 2001) and bind covalently to liver macromolecules leading to leakage of destructive hydrolytic proteases as calpains from dying cells (Chilakapati et al 2005).…”
Section: Discussionmentioning
confidence: 99%